PENGARUH IMPLEMENTASI BUDAYA KERJA (CATATAN LAPORAN CAPAIAN KINERJA HARIAN) TERHADAP PENINGKATAN KINERJA PEGAWAI PADA IAIN BENGKULU - Khairiah Khairiah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The purpose of this research was  to describe the  influence of work culture  (note  on report  of daily performance achievements) toward employees’ performance at  IAIN Bengkulu.  This research used  survey methods and  technical of path  analysis  through  SPSS. The samples in this study were  24 employees in IAIN Bengkulu.  The samples were  taken  using proportional random sampling  technique. The results  showed that there  is a direct effect of the positive and significant correlation between workplace cultures (note  on report of daily performance achievements) on employees’ performance in IAIN Bengkulu.  Based  on these results,  the researcher suggests the need to maintain the employees’ performance in IAIN Bengkulu in the future the need to maintain and  enhance the cultural  quality of work through  the budget  provision or application toward note on report of daily performance achievements through  online. To the leader as the direct supervisor  is expected to constantly monitor,  evaluate and know  by affixing a signature every day to his each  subordinates then  note on report  of daily performance achievements of employees there  is conformity  duties  between SKP (target  of employees’ performance) / labor contract in the earlier year with a record that is done  every day by employees. The  employees of IAIN Bengkulu  are  expected to  always  make the  note  on  report  of daily  performance achievements every day in accordance with their duties and functions  as well as responsibilities in the work